Morbidity and Mortality after Colorectal Surgery for Cancer - Angelucci, Giulio P.; Sinibaldi, Giovanni; Orsaria, Paolo; Arcudi, Claudio; Colizza, Sergio (Scientific Research, 2013)
Colorectal Cancer is the second most common cancer in western countries and, currently, surgical resection is still the principal treatment for this pathology. However, the operation carries significant morbidity and mortality, which is associated with an enormous use of healthcare resources. The aim of our study is to evaluate the incidence and the management of complications, and to understand how pre-exisiting comorbidities can influence the recovery of the patients. Between 2007 and 2012, a total of 534 patients underwent elective or emergency surgery for colorectal cancer in our department. Patients were identified for this study from a prospectively entered computerized database. Case notes of patients documented comorbidities, type of surgery performed, complication in the early postoperative period (30 days after surgery) and the management. Postoperative morbidity affected 89 patients (17%), of these 25 (27%) were anastomotic leakage (AL). 22 (24%) patients experienced intra-abdominal abscess. 16 patients (17%) had wound infections. 11 patients (13%) experienced post-operative bleeding and five of them had a re-operation within the I and the II day after surgery. 12 (13%) complained medical (cardiologic/respiratory) complications. We had 1 (1%) Small Bowel Obstruction, treated with a conservative therapy. Reoperation rate was 3% with 11 for AL, and 5 for bleeding. The mortality rate was 0.55% (3 patients). In our experience, we evidenced that surgery performed for advanced rectal cancer in the lower rectum, especially in urgency settings is associated with an increase of morbidity and mortality in the early post-operative period. Pre-existing comorbidities are involved in the morbidity of the patients, and a more accurate approach both in surgical technique and in the post-operative management can be proposed to the surgeon. Derivative stoma in high risk patients gave us the possibility of a conservative treatment of the Anastomotic Leak, the most common complication in our study, with antibiotics and CT-drainage.
Keywords: Colorectal; Colorectal Surgery; Morbidity; Mortality; Surgery; Complications; Early Post-Operative Complication; Management; Anastomotic Leak; Leakage